Bentuk Toleransi Antarumat Beragama Pada Siswa - Ni Putu Alit Wulandari; I Gede Suwindia; I Ketut Sudarsana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
Students of SMA Negeri 1 Kediri have established togetherness to foster harmony in plurality in the form of tolerance, realized the religious tolerance education among students in SMA Negeri 1 Kediri, Kediri District, Tabanan Regency. This study aims to gain knowledge about religious tolerance education among students in SMA Negeri 1 Kediri as a form of religious education among religious believers who are in the school environment to be developed and maintained as a stock later when it becomes a member of the community. This research includes the type of qualitative research with research data sourced from primary data and secondary data. Data were collected using participant observation techniques. Interviews that are used by researchers are structured interviews. Data analysis through three stages namely: data reduction, data presentation, and take conclusions. In summary, the results of this study can be summarized as follows: the form of religious tolerance education among students, in the form of: (1) school curriculum and policy, namely learning activities of character and religious education; (2) social activities, Culture and Sport, ie social activities that are done ismutual cooperation, Culture such as follow extracurricular art, Sports for example like togetherness exercises in game of soccer, volleyball, basket or futsal; (3) exemplary, ie the citizens of the school provide a good example to the students; and (4) group learning, ie in the teaching and learning process students are divided into several groups with adjusting amounts; (5) student orientation period by holding lecture and line up practice. The school community support for the implementation of religious tolerance education among students, namely: (1)principal; (2) the board of teachers; (3) staff staff, (4) students; (5) Union of Parents Guardian (POM); (6) support the school environment. The impact of implementing religious tolerance education among students, among others: (1) the introduction of heterogeneity; (2) strengthening the development of tolerance education; (3) strengthening of faith; (3) the strengthening of brotherhood.